Infecção de corrente sanguínea relacionada ao uso de cateteres venosos centrais em pacientes pediátricos de um hospital terciário - Pierotto, Aline Aparecida da Silva (2014)
Objective: To analyze the risk factors of blood stream infections of patients with positive blood cultures of central venous catheters (CVC). Methods: Retrospective descriptive study, with analysis of medical records and laboratory tests, which examined 28 patients with 44 blood cultures positive CVC. The variables were: age, gender, reason for hospitalization, length of hospital stay, type of catheter, micro-organism with sensitivity, antimicrobial resistance and outcome. Results: We analyzed 28 patients who had positive blood cultures in the CVC, and who did not have clinical or laboratory diagnosis of any other focus, 321 patients had negative blood cultures, and only 28 with positive blood cultures in the periphery and CVC (paired samples). The identified risk factors for infections related to catheters were age less than 1 year of patients (8.3 vs 23 months, the uninfected, p <0.01), catheter usage time (16 vs. 7 days; p <0.01) and length of stay in PICU (25 vs 6 days; p <0.01). The greater involvement of the catheters were short double lumen residence and located in the right subclavian. The most diagnosed bacteria in blood cultures of these patients were Sthaphylococcos epidermidis Staphylococcus aureus and that showed high resistance to oxacillin and sensitivity to vancomycin. Conclusions: The rate of bloodstream infection associated with the use of central venous catheters in intensive care units and pediatric ward is significantly affected by presençao the central venous catheter. The bloodstream infections are important causa de morbidity and mortality in pediatric patients and premature removal of the central venous catheter is important for the prevention of such infection.